The Influence of the Performance of the Satreskrim Tipidum Unit on the Disclosure of the Crime of Theft with Addiction in Mojokerto (Indonesian Journal of Police Studies, 2024)
Indonesia is a state of law, where law enforcement is enforced and often related to criminal offences. As is the case with the problem of the crime of theft with aggravation at Mojokerto Police Station. The purpose of this study is to describe and analyse the condition of organisational resources that support the performance of the Tipidum Unit and identify factors that affect the effectiveness of performance by the Tipidum Unit of Mojokerto Police to increase the disclosure of aggravated theft. The method in this research is qualitative, where data collection is done through interviews, observations, and documentation studies in the Tipidum Unit. Data validity is in the form of triangulation of sources and techniques. Data analysis methods include data reduction, data presentation, and conclusion drawing. The results of this study indicate that the effectiveness of the performance of the Mojokerto Police Tipidum Unit includes performance concepts, namely productivity, human resource value, and motivation, which are said to be ineffective. Factors affecting the performance of the Tipidum Unit based on SWOT theory show the many obstacles that cause performance in increasing the disclosure of the crime of theft with aggravation is still considered ineffective.
Keywords: Efektifitas, Pengungkapan, Curat, Unit Tipidum Satreskrim Polres Mojokerto